A mídia podcast como instrumento de divulgação científica da educação profissional e tecnológica brasileira - RAMOS, Rogério Luiz da Silva (Instituto Federal do Amapá, 2021)
Adopted from the premise of the distance between the scientific community and people in general, over time, Scientific Divulgation has been presented as an alternative for the construction of knowledge for the general public. Thus, with the commercial diffusion of the Internet, this communicative effort finds greater space to develop. Within this context and, given the current possibilities, the present work selects the media podcast as a tool for the popularization of the scientificity of its central object, the Brazilian Professional and Technological Education. Thus, it aims to investigate the penetration of scientific divulgation of EPT in Brazil via podcasting through EPTCast, an Educational Product developed along the ProfEPT offered by IFAP, Campus Santana. Based on the directions of the concentration area Organizations and Memories of Pedagogical Spaces at EPT, the theoretical basis of this research exposes understandings of 03 areas of knowledge: Scientific Divulgation, Digital Communication, and Professional and Technological Education. In its methodological aspects, it is configured as quantitative-qualitative research that has the EPTCast account on the Anchor.fm platform as locus, a virtual space for hosting and distributing audio files. The results show that the highest numbers of hits come from episodes with themes specific to the Brazilian EPT. Regarding its reach, 93. 16% of the audience comes from Brazil, and the other part is distributed in 12 more countries. Concerning national distribution accesses, the sequence from the largest to the smallest Region in terms of accesses was North, Southeast, Northeast, South, and Midwest. Regarding digital tools, the 03 most used individual options were Spotify, Google Podcasts, and Castbox, and devices with the Android operating system were the most used to access the episodes. The age groups that most consumed the EPTCast content were 18 to 22 and 35 to 44 years of age. Regarding the genres, Males presented themselves as 50% of the listening public, Females 42%, and Others 8%. The considerations show that, given its results, this research proves to be successful and what is desired from here on is that this became a tool to support other EPT popularization initiatives in Brazil.